Evaluation of The South Sumatra Samsat E-Dempo Application using the System Usability Scale Method - Agustina, Merry; Aqdi, Syahanan (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
E-Dempo Samsat South Sumatra is an online vehicle tax payment application from the South Sumatra Regional Revenue Agency (Bapenda). Through the E-Dempo Samsat application, users can make tax payments without having to make payments to the local Samsat, as well as in the application, users can check vehicle data and the total tax value, and can make complaints related to vehicle tax. This study aims to determine the usability level of the E-Dempo Samsat application at which level from the user's point of view. Using the system usability scale (SUS) method, this study provides evaluation results to ascertain the level of usability of the South Sumatra Samsat E-Dempo application. Data analysis with a usability scale system (SUS) was used as the research method, and questionnaires were distributed as part of the quantitative approach. The results of this study are in the form of a score of the method (SUS) of 39 which states that the quality of the level of use of the E-Dempo Samsat application is still low.